Cleaning Oily Sludge Using Colloidal Gas Aphrons Optimizing Process Conditions and Analyzing Mechanisms - Ren, Hongyang (Langmuir : the ACS journal of surfaces and colloids, 2024)
Colloidal gas aphrons (CGAs) are applied in pollutant removal due to their large specific surface area and high surface activity. The structure and properties of the prepared CGAs were investigated in the process of oil removal from oily sludge. The prepared CGAs had a liquid film thickness was 5-10 μm with high stability. CGA interfacial tension was as low as 3.157 mN/m. Then it was found that the oil removal rate of CGAs was higher than that of chemical treatments, showing that CGAs could increase the mass transfer surface area and provide additional attachment sites for pollutants, enhancing the oil removal. The treatment conditions of the oil removal were optimized through response surfaces, showing that under optimal treatment conditions, the oil removal rate of oily sludge reached 96.07%. Additionally, the interaction between surfactant concentration and temperature was the most significant of all of the influencing factors. The behavior and mechanism of CGAs in the cleaning process of oily sludge were further investigated using an inverted fluorescence microscope, SEM, FTIR, and two-dimensional fluorescence spectrometer, showing that pollutants transferred from the liquid film surface of CGAs to the inside the film, and CGAs could specifically adsorb negatively charged organic compounds and aromatic hydrocarbons. The results show that CGAs achieved liquid membrane solubilization. Many negatively charged organic compounds and aromatic hydrocarbons are adsorbed onto the CGAs liquid membrane surface via electrostatic and hydrophobic interactions and then migrated to the hydrophobic layer of the CGAs liquid membrane due to the distribution effect, thus enabling rapid pollutant migration between solid and liquid phases